S126 The cell adhesion receptor CADM1 regulates other adhesion receptors in human mast cells. (2nd December 2011) - Moiseeva, E P; Leyland, M L; Bradding, P
Abstract : Introduction and Objectives: Cell adhesion molecule 1 (CADM1) contributes to adhesion, viability and adhesion-induced degranulation in mast cells. Severity of asthma correlates with accumulation of human lung mast cells in specific compartments, including airway smooth muscle (ASM). human lung mast cells adhesion to ASM is known to be mediated by CADM1, integrins and other receptors. Here we investigated the role of CADM1 in the cell-cell and extracellular matrix (ECM) adhesion of mast cells to primary ASM. Methods: The mast cell line HMC-1 was used in adhesion assays to primary ASM and ECM produced by these cells. ECM was prepared by hypotonic extraction with detergents to remove cell content. Modulation of CADM1 expression by adenoviral delivery in HMC-1 cells was verified by FACS and Western blotting. Cells with modulated CADM1 were examined in adhesion assays. Results: HMC-1 cells adhered to ASM in a time-dependent manner, reaching 92% and 70% adhesion at 1 h to ASM and ECM, respectively. Addition of EDTA resulted in a reduction of adhesion to ASM and ECM to 55% and 22%, respectively, indicating a major role of cation 2+ -independent receptors in cell-cell and integrins in ECM adhesion of mast cells. CADM1-overexpression did not change adhesion to ASM (98%), but decreased adhesion to ECM to 55%. CADM1 RNA interference in HMC-1 resulted in 60% reduction of surface CADM1 and complete loss of CADM1 determined by FACS and Western blotting, respectively, 6 days after transduction. CADM1 downregulation resulted in drastically reduced adhesion to both ASM and ECM down to 37 and 17%, respectively. Addition of EDTA further decreased adhesion to ASM and ECM to 13% and 6%, respectively. Thus, CADM1 downregulation drastically decreased net adhesion of mast cells. Conclusions: Mast cell adhesion receptor CADM1 plays a regulatory role in mast cell adhesion by affecting not only cell-cell adhesion, but also ECM adhesion.